Collaborative learning, using Facebook's page and Groups - Ataie, Farib; Shah, Asadullah; Mior Nazri, Mior Nasir (International Journal of Computer System, 2015)
This study designed, developed and evaluated an ICT artifact, including Facebook's page and groups based on Cruz and Carvalho framework for practicing collaborative learning. All features utilized, be evaluated by observations, Facebook metrics and interviews based on activities and interactions amongst students and all users on Facebook with design science research methodology (DSRM). This study shows students and learners could practice collaborative learning and regulate their knowledge in this platform and enhance their performance and self-regulations.